PENURUNAN KECEMASAN PASIEN ONE DAY SURGERY MENGGUNAKAN TERAPI MUSIK - Adin Mu’afiro; Kiaonarni O.W.; Endang Soelistyowati (Poltekkes Kemenkes Surabaya, 2014)
Anxiety increases the sympathetic stress response of patients before surgery. The purpose to analyze the music therapy effect to decrease anxiety a one-day surgery patient’s. The study design was a quasi-experiment with a design Randomized Controlled Trial of the double-blind. The samples were mostly patients undergoing ODS at the Hospital Haji Surabaya treatment group of 20 people and 20 people with a comparison control group of men and women, respectively 10. Dependent variable is the ODS patient anxiety. Independent Variable is the study of music therapy. The research instruments include State-Trait Anxiety Inventory, the music, MP4, headphones. Data analysis using a t -test. The results showed a difference in the average reduction between treatment and control groups (p=0.000). Patients who received treatment group music therapy decreased anxiety average of 5.90 whereas in the control group actually increased anxiety average of 1.65. Decreased patient anxiety due to musical stimuli stimulates alpha and beta waves depress the CNS that affects relax and lull. Suggested nurses provide patient comfort before surgery ODS use music song/type of rhythm he liked. Key words: anxiety, music therapy, one-day surgery